Bed Sharing. Issue 1 (January 2015) - Beal, Judy A.
<x xml:space="preserve">Abstract</x> Despite numerous public service campaigns and education for parents and providers, parents sharing their bed with their babies remains a pediatric health issue. Dr. Beal offers strategies for counseling new parents about bed sharing.